Analytical, Logit Model-based Examination of the Hungarian Regional Parallel Public Transport System - András Lakatos; Péter Mándoki (Promet - Traffic&Transportation, 2020)
The ongoing competition between bus and railway systems in the Hungarian regional passenger transport is a current problem, because these subsectors need to complement each other, instead of being in the government-funded competition. Long-term sustainability and efficiency in passenger transport require a balanced transport policy. The parallel bus and railway links, which are present in all regions of Hungary can result in competition. This research explores the solutions to this issue for long-term environmental and economic sustainability optimization. An objective index and interventions developed in previous studies have been applied here. This investigation is to validate the objective index and the interventions by using the Logit model.